COMPARISON OF CHLOROPHYLL CONCENTRATION ESTIMATION USING TWO DIFFERENT ALGORITHMS AND THE EFFECT OF COLORED DISSOLVED ORGANIC MATTER - Bisman Nababan (National Institute of Aeronautics and Space of Indonesia (LAPAN), 2008)
The effect of colored dissolved organic matter (CDOM) on the Sea-viewing Wide Field-of-view Sensor(Sea WiFS) OC4v4 and the MODIS algorithms used to estimate chlorophyll-a was studied using satellite and situ data collated during seasonal cruises in the Northeastern Gulf of Mexico between 1997 and 2000. For chlorophyll-a concentrations 50 mg m, OC4v4 generally overestimated chlorophyll-a concentration by up to 300 percent. The MODIS algorithm provided better estimates of high CDOM concentration, found typically nearshore in noterhn summer and spring. For oceanic waters where chlorophyll-a concentrations 1.0 mg m, both OC4v4 and MODIS algorithm had errors within the Sea WiFS mission specification (35 percent) during fall. The OC4v4 algorithm is more susceptible to artifacts due to CDOM absorption of light at 443 mm. Keywords: chlorophyll-a, Mississippi River Plume, Sea WiFS, upwelling, OC4v4.